The impact of shared decision making on transitional preparation in children with recurrent pneumonia - Zhang, Fan; Li, Nan; Kang, Yang; Wang, Xing; Zhao, Yanru (Frontiers in Medicine, 2025)
ObjectiveThis study evaluates the impact of Shared Decision-Making (SDM) on transitional preparation in children with recurrent pneumonia, highlighting its relevance to precision medicine.MethodsThis retrospective cohort study conducted following the Strengthening the Reporting of Observational Studies in Epidemiology reporting guideline, included 124 children with recurrent pneumonia who were hospitalized between January 2023 and February 2025. Participants were divided into two groups based on the treatment they received: a control group that underwent standard nursing care and an observation group that received SDM interventions. Transition readiness and quality of life (measured by PedsQL 4.0) were assessed and compared between the two groups at three intervals: pre-intervention, 1 month post-discharge, and 3 months post-discharge.ResultsA total of 120 children completed the study, with 60 in each group. Transition readiness improved significantly over time, with main effects for time (Ftime = 147.329, P < 0.05), group (Fgroup = 15.384, P < 0.05), and a significant interaction effect (Finteraction = 7.338, P < 0.05). The observation group consistently demonstrated higher readiness levels. PedsQL4.0 scores showed similar trends (Ftime = 112.387, P < 0.05; Fgroup = 10.842, P < 0.05; Finteraction = 8.623, P < 0.05), favoring the observation group.ConclusionShared Decision-Making enhances transition readiness and quality of life in children with recurrent pneumonia, highlighting its value in precision medicine. These findings support the need for longitudinal studies, SDM training in pediatric education, and policy guidelines to promote SDM, fostering patient-centered care.